2014
DOI: 10.17265/2159-5836/2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Music Learning With Digital Tools: A Case Study of a Student Using iSCORE

Abstract: iSCORE is a digital tool, available without charge, which was designed for students who take lessons from independent music teachers. One of the challenges of this learning format is that students must develop strategies to practice on their own between lessons. iSCORE can help meet that challenge by supporting students as they develop strategies for self-regulation to enhance their goal-setting, practice strategies, and abilities to reflect and critique their progress. This paper describes a case study of a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Lastly, ePEARL has been adapted for use by studio music teachers and their students, called iSCORE, and research is underway on its use within arts education (Upitis, Abrami, Brook, Troop, & Varela, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, ePEARL has been adapted for use by studio music teachers and their students, called iSCORE, and research is underway on its use within arts education (Upitis, Abrami, Brook, Troop, & Varela, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Very often these technologies are considered an added value to the teaching and learning process. Arguments to backup the belief in their educational potential concern, for example, the multimodal presentation of learning content as supporting the processing of learning content ( de Jong 2010;Mayer et al 1999;Sweller, Van Merrienboer, and Paas 1998), the use of objective measurement as a way to bypass the possible ambiguity of conventional verbal feedback (Hoppe, Sadakata, and Desain 2006;Howard et al 2007), the facilitation of creating a powerful learning environment (Bransford 2000) and their appeal to young people (Burnard 2007;Prensky 2001;Upitis, Brook, and Abrami 2014;Wise, Greenwood, and Davis 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The use of recordings has also been investigated—specifically how this practice can influence the self-regulated learning of prospective piano teachers (Deniz, 2012)—although it has been suggested that on numerous occasions students do not subsequently resort to viewing practice recordings (Waddell & Williamon, 2019). The use of a digital portfolio, such as electronic reflections and goals or asynchronous electronic communication with the teacher, has also been the subject of research to find out how it influences instrumental self-regulated learning (Brook & Upitis, 2015; Upitis & Abrami, 2017; Upitis et al, 2010, 2014, 2017).…”
Section: Self-regulation Music Learning and Technologymentioning
confidence: 99%